A Bibliometric Analysis of Sustainable Village Tourism Development Strategy Researches from 2019 to 2024 - Suardana, I Ketut; Adiyanti, Assyifa Shafia; Widodo, Wahyu Indro; Anggraini, Fera Dhian; Ardanari, Francisca Ratna; Disma, Fatimatuz Zahra (Journal of Information Systems Research and Practice, 2024)
This study presents a bibliometric analysis which focusing on village tourism development strategy. It presents a comprehensive abstract, offering a synopsis of both research findings and methodological approaches employed in the analysis. The core objective revolves around the discernment of pivotal themes and emerging trends within the sphere of sustainable tourism, with a specific focus on rural locales. Utilizing VOS Viewer as our main vehicle tool for bibliometric analysis and leveraging data from Scopus, we accentuate the significance of environmental, economic, and social sustainability in the developmental trajectory of village tourism. Furthermore, the study underscores the integral role of community participation and collaborative efforts in realizing the objectives of sustainable tourism, aligning with the broader goals of environmental conservation and community well-being. These findings contribute substantively to the ongoing scholarly discourse surrounding sustainable tourism practices, thereby furnishing valuable insights for policymakers, researchers, and practitioners engaged in this dynamic and critical field.